2020
DOI: 10.1016/s2215-0366(20)30047-x
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of medical workers in Wuhan, China dealing with the 2019 novel coronavirus

Abstract: psychological protection of the mental health of medical workers has been initiated in China. The experiences from this public health emergency should inform the efficiency and quality of future crisis intervention of the Chinese Government and authorities around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

63
1,587
13
206

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,788 publications
(1,869 citation statements)
references
References 3 publications
63
1,587
13
206
Order By: Relevance
“…Maintaining staff mental health is essential to better control infectious diseases, although the best approach to this during the epidemic season remains unclear. 4,5 The learning from these psychological interventions is expected to help the Chinese government and other parts of the world to better respond to future unexpected infectious disease outbreaks.…”
mentioning
confidence: 99%
“…Maintaining staff mental health is essential to better control infectious diseases, although the best approach to this during the epidemic season remains unclear. 4,5 The learning from these psychological interventions is expected to help the Chinese government and other parts of the world to better respond to future unexpected infectious disease outbreaks.…”
mentioning
confidence: 99%
“…Émergence des troubles Comme pour l'épidémie SARS-CoV-1, il est à craindre que certains soignants, notamment les soignants de première ligne, présentent à distance de la crise sanitaire, des symptômes psychiatriques de nature diverse : anxiété, stress aigu, TSPT, symptômes dépressifs (12,21,22). En effet, un an après l'épidémie de 2003, les soignants ayant pris en charge des patients infectés avaient une prévalence augmentée d'épuisement professionnel, de détresse psychologique et de symptômes de TSPT (13).…”
Section: Risques Psychologiques Chez Les Soignants Exposés Au Covid-19unclassified
“…At present, it has been reported that many local hospital workers in Wuhan, especially nurses, have been confronting occupational exhaustion. Inevitably, the overloaded working conditions lead to mental health problems such as serious psychosomatic disorders and a decline in decision making and execution [9]. Psychological services and crisis interventions are needed at an early stage to reduce anxiety, depression, and post-traumatic stress disorder (PTSD) in almost all groups during such a stressful period.…”
Section: Possible Coping Strategiesmentioning
confidence: 99%